Armadillos. - Schuetz, Kari. (Minneapolis, MN : Bellwether Media, 2012)
Simple text and color photographs introduce young readers to armadillos, looking at what they are, where they live, what they eat, and how they avoid predators.
Includes bibliographical references and index.
Keywords: Armadillos